Bahasa yang Membentuk Jati Diri dan Karakter Bangsa - Oktavianus Oktavianus (Masyarakat Linguistik Indonesia Universitas Andalas, 2013)
This short article is an attempt to identify and discuss the types of language that can shape the identity and character of the nation. The analysis is done by looking at the relationship between language and culture. The result of the analysis indicates that language, both proverbs and nonproverbs, contains values. The values are transferred into attitude, behavior and habit to shape the identity and character of the nation.